Biosurfactant production by Pseudomonas aeruginosa MSIC02 in cashew apple juice using a 24 full factorial experimental design - Rocha Maria Valderez Ponte; Mendes Jocélia Sousa; Giro Maria Estela Aparecida; Melo Vânia Maria M.; Gonçalves Luciana Rocha Barros (Chemical Industry and Chemical Engineering Quarterly, 2014)
In this work, the production of biosurfactants from cashew apple juice by P. aeruginosa MSIC02 was investigate by carrying out a 24 full factorial experimental design, using temperature, glucose concentration from cashew apple juice, phosphorous concentration and cultivation time as variables. The response variable was the percentage of reduction in surface tension in the cell-free culture medium, since it indicates the surface-active agent production. Maximum biosurfactant production, equivalent to a 58% reduction in surface tension, was obtained at 37°C, with glucose concentration of 5.0 g/L and no phosphorous supplementation. Surface tension reduction was significant, since low values were observed in the cell-free medium (27.50 dyne/cm), indicating that biosurfactant was produced. The biosurfactant emulsified different hydrophobic sources and showed stability in the face of salinity, exposure to high temperatures and extreme pH conditions. These physiochemical properties demonstrate the potential for using biosurfactants produced by P. aeruginosa MSIC02 in various applications.